Identification of Student Learning Difficulties Based on Self, Environment, and Family Aspects in Learning Mathematics at the Elementary School Level - sholihah, Neneng; Iklimatunnajah, Iklimatunnajah; Hartanti, Fauzia Dewi; Pitriyani, Pipit (PT Ilmu Inovasi Nusantara, 2023)
Basic education is an important foundation for students' academic and social development. Not all students experience ease in obtaining and processing the information taught at school. Education is also the most important factor for the progress of a nation. Student learning difficulties are not only caused by low cognitive factors but are evidenced by deviant behavior or external factors that they experience, such as family and environmental support factors. Family and environmental support can also play an important role in overcoming learning difficulties for elementary school students. This study used a quantitative research design with a cross-sectional approach. This study uses a descriptive approach design that aims to describe and analyze the phenomenon of learning difficulties of elementary school students. The population of this research is the Suradinaya elementary school. Random sampling technique has been used in this study. The instrument used was a learning difficulties questionnaire as a research measurement tool. Based on the diagram above, it can be seen that aspects of the child's self and family aspects have almost the same average percentage, with values of 66% and 65%. Environmental aspects get a higher average percentage, which is equal to 75%. There needs to be cooperation between schools, families, and the surrounding environment in creating a conducive and effective learning environment for students. In conclusion, student learning difficulties are influenced by various factors, both from aspects of the student's self as well as environmental and family factors. Thus, students will be able to achieve maximum academic achievement and achieve success in the future